The CD95(APO-1/Fas) DISC and beyond - Peter, Marcus E.; Krammer, Peter H. (Cell death and differentiation, 2003)
CD95 (APO-1/Fas) is a prototype death receptor characterized by the presence of an 80 amino acid death domain in its cytoplasmic tail. This domain is essential for the recruitment of a number of signaling components upon activation by either agonistic anti-CD95 antibodies or cognate CD95 ligand that initiate apoptosis. The complex of proteins that forms upon triggering of CD95 is called the death-inducting signaling complex (DISC). The DISC consists of an adaptor protein and initiator caspases and is essential for induction of apoptosis. A number of proteins have been reported to regulate formation or activity of the DISC. This review discusses recent developments in this area of death receptor research.